Design, Synthesis, and Antitumor Activity of Novel Acylate of 6-OH at 1- O-acetylbritannilactone - Liu, Shouxin; Feng, Jun; Liu, He; Li, Junzhang; Tian, Xia (Medicinal Chemistry, 2015)
N-(α-Alkyloxime-3-phenylpropionyl) proline was designed and synthesized as an acylating agent to modify the 6-OH of 1-O-acetylbritannilactone. Eight intermediates and eight target compounds were obtained. The structures of sixteen novel compounds were characterized by 1HNMR, IR and HRMS. The activities against HL-60 and Bel-7402 cell lines were tested, the IC50 values of compound IVg were 2.7 μM and 4.3 μM, respectively.
Keywords: Acylation compound